ATIVIDADE ANTICARCINOGÊNICA DE EUPHORBIA TITHYMALOIDES USANDO LINHAGENS DE DROSOPHILA MELANOGASTER - MIRANDA, Andressa da Silva Miranda; GUTERRES, Zaira da Rosa; FIGUEIREDO, Patrícia de Oliveira; SOARES, Luzinátia Ramos; GARCEZ, Walmir Silva; GOUVEIA, Juceli Gonzalez (ANAIS DO ENIC, 2025)
-